Strategy of the TNI AD Regional Units in Overcoming Social Conflict and Return Of Refugees of Kariu Residents, Central Maluku (Case Study: Military Command 1504/Ambon 2022-2023) - Hem Chhaty; Hikmat Zakky Almubaroq; Panji Prawira Asa Kusumah (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the strategies implemented by Military Comand 1504/Ambon in addressing social conflicts and the repatriation of Kariu refugees on Haruku Island, Central Maluku Regency, during the 2022-2023 period. The social conflict between the residents of Kariu and Pelauw, as well as Ory, led to the displacement of thousands of Kariu residents. To restore security and facilitate the return of refugees, military command 1504/Ambon collaborated with the Ambon City Police and the Central Maluku Regency Government, supported by the community, ministries and other institutions. This research uses a qualitative approach with a case study method, involving interviews, observations, and document analysis. The results show that Military command1504/Ambon's active role in conflict mediation, security protection, and humanitarian aid provisions was crucial in the repatriation process and maintaining post-conflict peace. The implemented strategies proved effective in addressing refugee challenges, although some resistance from local communities persisted.